Immune Checkpoint Inhibitors and Radiotherapy in NSCLC Patients: Not Just a Fluke - Lorenzo Belluomini; Francesco Fiorica; Antonio Frassoldati (Oncology and Therapy, 2019)
Abstract The discovery of immune checkpoint inhibitors (ICIs) such as programmed cell death protein 1 (PD-1) inhibitors, nivolumab and pembrolizumab, and programmed cell death ligand 1 (PD-L1) inhibitors, atezolizumab and durvalumab, has revolutionized the treatment of advanced non-small cell lung cancer (NSCLC). Concurrent radiotherapy (RT) is of particular interest with regard to the potential role for this combination in many settings. The purpose of this commentary is to evaluate the potential for the combination of immune checkpoint inhibitors and radiotherapy, including analysis of studies that have considered this combination in various settings.